Determinants of Coffee Farmers’ Income: The Role of Land Area and Production Volume in Pargarutan Jae Village - Naimatul Lubis; John Nefri; Heri Faisal Harahap; Reza Mardiyah Amir (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2025)
This study aims to analyze the effect of production land area on the income of coffee farmers in Pargarutan Jae Village, South Tapanuli Selatan. The method used is a quantitative approach involving 109 coffee farmer respondents selected using the accidental sampling method. Data were collected through questionnaires, observations, and documentation, then analyzed using Structural Equation Modeling Partial Least Square (SEM PLS). The results show that the production land area has a significant influence on increasing coffee production, which in turn positively impacts farmers’ income. The majority of farmers have a last education level of vocational high school/general senior high school and are in productive age, with most incomes at the lower-middle level. The validity and reliability of the research instruments have been well tested, with loading factor and AVE values meeting the criteria for convergent and discriminant validity. These findings indicate that managing and increasing the production land area is a key factor in improving the welfare of coffee farmers in the area.